2020
DOI: 10.1099/jgv.0.001435
|View full text |Cite
|
Sign up to set email alerts
|

Update: proposed reference sequences for subtypes of hepatitis E virus (species Orthohepevirus A)

Abstract: In this recommendation, we update our 2016 table of reference sequences of subtypes of hepatitis E virus (HEV; species Orthohepevirus A, family Hepeviridae) for which complete genome sequences are available (Smith et al., 2016). This takes into account subsequent publications describing novel viruses and additional proposals for subtype names; there are now eight genotypes and 36 subtypes. Although it remains difficult to define strict criteria for distinguishing between virus subtypes, and is not within the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
377
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(429 citation statements)
references
References 27 publications
4
377
1
1
Order By: Relevance
“…Taxonomically, the family Hepeviridae is divided into the genus Orthohepevirus with the species Orthohepevirus A, B, C , and D , and the genus Piscihepevirus . The species Orthohepevirus A contains eight distinct genotypes that infect humans and other mammals [ 10 ]. It is known that HEV-1 to -4 infect humans, and rare cases of human infection with other genotypes like HEV-7 have also been described [ 11 , 143 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Taxonomically, the family Hepeviridae is divided into the genus Orthohepevirus with the species Orthohepevirus A, B, C , and D , and the genus Piscihepevirus . The species Orthohepevirus A contains eight distinct genotypes that infect humans and other mammals [ 10 ]. It is known that HEV-1 to -4 infect humans, and rare cases of human infection with other genotypes like HEV-7 have also been described [ 11 , 143 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…HEV-3 is common among pigs worldwide, which constitute the major reservoir for human infections [ 164 , 165 ]. HEV-4 is widely distributed in South and East Asia, where both wild and domesticated pigs serve as a reservoir [ 10 , 158 , 166 ]. Infection rates are high in people over 50 years of age [ 4 , 167 , 168 ], and seroepidemiological studies found no significant differences in HEV-IgG seropositivity according to gender [ 169 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Orthohepevirus A species (Smith et al, 2020) makes it difficult to use molecular assays for the diagnosis of HEV infection. Nevertheless, there are currently many in-house and commercial assays that allow for detection of the majority of the HEV strains.…”
Section: The Wide Variety Of Genotypes and Subtypes In Thementioning
confidence: 99%
“…HEV belongs to the Hepeviridae family, a family that has two genera: the Orthohepevirus (mammalian and avian strains), with four species ( A – D ), and the Piscihepevirus (cutthroat trout virus) [ 7 , 8 ]. Humans are infected by Orthohepevirus A, although several cases of Orthohepevirus C infection have been reported recently [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%